Factors affecting the production, germination and viability of Cylindrocladium quinqueseptatum spores - Jayasinghe C K; Wijesundera W L C (Indian Journal of Natural Rubber Research, 1995)
Cylindrocaldium quinqueseptatum, a pathogen of Eugenia caryophyllata and Hevea brasiliensis produced spores freely when grown on artificial media under a normal dark and light regime and under continuous dark. CDA and LBA were found to be suitable media for sporulation. Spore production occurred between 20 C and 35 C with an optimum at 30 C. Ten minutes exposure of spores as wet smears to UV (253.7 nm) significantly inactivated spores. The most critical factor which influenced the spore viability and germination was humidity. Free water was found to be essential for spore germination and germination dropped to 2.5 per cent even at high humidities (96;). Spores lost viability by 25 per cent within a period of two minutes and 90 per cent after 9 minutes, when stored as dry smears. On leaves, typical lesions were produced only at 100 per cent humidity. Size of the lesions at 96 per cent humidity was negligible and no lessions were produced at 91 per cent RH. Spore germination occurred between 10 C to 35 C. The largest lesions on leaves resulted at 25 C and at room temperature (28+_2 C) when inoculated as wet smears. Wet smears of spores could withstand high temperatures of 40 C for 2 h without loss of viability. The results of this investigation suggest that Cylindrocladium infections are likely to reach epidemic proportions during monsoon periods of dull, overcast, rainy weather
Keywords: Cylindrocladium quinqueseptatum; Eugenia caryophyllata; Hevea brasiliensis; Spore production